The Contribution of Organizational Culture towards Teachers' Organizational Citizenship Behavior - Rr. Astri Indriana Octavita; Satrianta, Hengki; Tiarma Ika Yuliana (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
Organizational citizenship behavior is an important behavior that teachers should have. In fact, there are still teachers who have not been able to implement this behavior. It is believed that organizational culture has a relationship with this phenomenon. It is necessary to further explore how organizational culture contributes to organizational citizenship behavior in teachers. This study was conducted using a quantitative survey approach. The study involved 195 samples drawn through proportional random sampling. Data were collected through organizational culture and organizational citizenship behavior scales. The data were statistically analyzed both through descriptive statistics and inferential statistics to answer the research hypothesis. The results showed that organizational culture has a positive and significant effect on organizational citizenship behavior in teachers. Efforts are needed to always strengthen organizational culture so that organizational citizenship behavior in teachers remains in an optimal condition.